Reduction in Fuel and Power Consumption in a Traveling Grate Pelletizing Furnace Through Computer Control - R. C. Corson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1984)
Modern microprocessor systems make it possible to use several variables to anticipate changes in the process and to react with responses before upsets can be magnified by the process or by control action. Through tighter control, "insurance" can be eliminated from process set points without affecting product quality. In actual operation with a traveling grate furnace this control philosophy has produced savings of up to 20% in fuel consumption and 8% in fan power usage while producing a more consistent quality product.